EKSPLORASI KEARIFAN LOKAL MELALUI TEKS NARATIF: STUDI RITUAL TEKES MASYARAKAT SUKU LAMASI DALAM PEMBELAJARAN BAHASA INDONESIA - Katharina Nay; Florianus Aloysius Nay; Rudobertus Talan (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2025)
This study aims to explore the local wisdom values contained in the Tekes traditional ritual of the Lamasi people in Insana District, North Central Timor Regency, and to explore its potential as a narrative text in Indonesian language learning. The research approach used is descriptive qualitative with narrative ethnography. Data were collected through in-depth interviews, participatory observation, documentation, and literature studies. The results show that the Tekes ritual is a form of respect for ancestors carried out through cultural symbols such as hauteas, nyiru, traditional cloth, betel nut, and sacrificial animals. Each symbol contains values such as religiosity, solidarity, respect for ancestors, and spiritual strength. The narrative structure of the Tekes procession includes elements of orientation, complication, resolution, and coda, which are in accordance with the basic competencies of narrative texts in the Indonesian language curriculum. The integration of Tekes as teaching material can strengthen student literacy while building cultural awareness and local identity. This study recommends the need for the development of local wisdom-based learning and cultural preservation by communities and educational institutions collaboratively.